The Relationship between Caries-Specific Quality of Life and Generic Wellbeing in a Dutch Pediatric Population - Helen J. Rogers; Jan H. Vermaire; Fiona Gilchrist; Annemarie A. Schuller (MDPI AG, 2019)
Dental caries has significant negative impacts on the lives of children and young people. Whilst the impacts on children’s oral health-related quality of life (OHRQoL) have been increasingly investigated, the effect on children’s overall wellbeing remains largely unknown. Data were obtained from a survey conducted across four cities in the Netherlands. Children and their parents completed a series of questionnaires, which included Dutch versions of a caries-specific pediatric measure of OHRQoL (CARIES-QC-NL) and a generic pediatric health utility measure (CHU9D-NL). The participating children underwent dental examinations to determine their caries status. A total of 486 11-year-old children participated in the study, of which 184 had caries experience (38%). The mean number of decayed, missing and filled teeth (DMFT) was 0.71. The CARIES-QC-NL was found to have statistically significant correlations with the DMFT and CHU9D-NL. There were no statistically significant correlations between the CHU9D and the clinical variables. The CARIES-QC-NL had acceptable internal consistency and construct validity in this population despite the low prevalence of active caries. A relationship was demonstrated between OHRQoL and generic wellbeing in this population. Despite this, the CHU9D did not show any correlation with the clinical data, which may limit its application in studies of the impact of dental caries.